Time Discipline Character Education for Students According to the book Ngudi Susilo by KH. Bisri Mustofa - Ali Mahbub; Amir Mukminin (Yayasan Azhar Amanaa Yogyakarta, 2025)
This research aims to analyze the concept of time discipline character education for students according to the book Ngudi Susilo and its relevance in the formation of student character in the modern era. Ngudi Susilo's book is one of the works of moral education that emphasizes the importance of ethics, manners, and discipline in daily life. The research method used is qualitative research with a library research approach. The main source of data comes from the book of Ngudi Susilo, while supporting data is obtained from various literature related to character education and time discipline. Data analysis techniques are carried out through data reduction, data presentation, and descriptive-analytical conclusions. The results of the study show that the character education of time discipline in the book of Ngudi Susilo is realized through the habit of living an orderly life, respecting time, responsibility for tasks, and obedience to the rules. These values are taught through example, advice, and habituation of positive behavior. This concept is relevant to be applied in the world of education today as an effort to form students who are disciplined, responsible, and have noble character. Thus, Ngudi Susilo's book has an important contribution in strengthening character education, especially in building time discipline in students.